Mathematics: What’s Spatial, What’s Not - Arlinghaus, William C. (Quaestiones Geographicae, 2015)
Probably, almost everyone has some idea of what is meant by the words ‘spatial mathematics.’ The problem is that 100 people have 100 different ideas, because the concept is not easy to codify. In this paper we suggest a few ways to illustrate differences between ‘spatial’ and ‘non-spatial’ concepts, and ways to introduce spatial approaches where none was present before.